2021
DOI: 10.1111/dom.14335
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the need for carbohydrate counting in type 1 diabetes using closed‐loop automated insulin delivery (artificial pancreas) and empagliflozin: A randomized, controlled, non‐inferiority, crossover pilot trial

Abstract: Aim To assess whether adding empagliflozin to closed‐loop automated insulin delivery could reduce the need for carbohydrate counting in type 1 diabetes (T1D) without worsening glucose control. Materials and Methods In an open‐label, crossover, non‐inferiority trial, 30 adult participants with T1D underwent outpatient automated insulin delivery interventions with three random sequences of prandial insulin strategy days: carbohydrate counting, simple meal announcement (no carbohydrate counting) and no meal annou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
(79 reference statements)
0
20
0
2
Order By: Relevance
“…89 Though postprandial glucose levels were not reported for Haidar et al (see Table 2), the daytime time-in-range and standard deviation were significantly reduced in the empagliflozin 25 mg group on HCL compared to placebo on HCL. 86 In Biester et al 85 the areas under the curve for both meals were reduced in the dapagliflozin group compared to placebo, as was standard deviation of glucose.…”
Section: The Benefits Of Sglt Inhibitor Use In Closed-loop Therapymentioning
confidence: 92%
See 2 more Smart Citations
“…89 Though postprandial glucose levels were not reported for Haidar et al (see Table 2), the daytime time-in-range and standard deviation were significantly reduced in the empagliflozin 25 mg group on HCL compared to placebo on HCL. 86 In Biester et al 85 the areas under the curve for both meals were reduced in the dapagliflozin group compared to placebo, as was standard deviation of glucose.…”
Section: The Benefits Of Sglt Inhibitor Use In Closed-loop Therapymentioning
confidence: 92%
“…Two studies have used dapagliflozin and empagliflozin as adjunct to closed-loop therapy. 85,86 In the study described in Biester et al 85 dapagliflozin 10 mg BID (2 doses) was used as adjunct to fully closed-loop; participants were given 2 mixed meal tests 6 hours apart without meal announcement. The TIR with dapagliflozin was 68% compared to 50% in the placebo arm ( P < .001), and required 22% less insulin.…”
Section: Sglt Inhibitor Use and Closed-loop Therapy: Research Thus Farmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the use of fully closed-loop systems in T1D have shown this to be a safe and effective approach to achieving target glucose outside post-prandial periods, however mitigation of post-prandial hyperglycemia remains a challenge. [45][46][47] Further studies are ongoing (NCT04877730, NCT04545567) to investigate fully closed-loop, and with the advent of faster acting insulins and dual-hormone systems, fully closed-loop therapy for T1D may become a reality in the near future.…”
Section: Future Directionsmentioning
confidence: 99%
“…Of note, mean fasting ketones levels were higher in participants when on empagliflozin (3.96 ± 3.24 vs. 2.34 ± 1.98 mg/dl; P < .001), but there was no occurrence of ketoacidosis. 53 Overall, strong evidence for the use of SGLT2 inhibitors as an adjunctive therapy to CL glucose control is limited, and the increased risk of ketoacidosis presents a great concern.…”
Section: Sodium-glucose Co-transporter (Sglt) Inhibitorsmentioning
confidence: 99%